The Concept of Islamic Education According to Buya Hamka and Its Relevance to the Era of Society 5.0: Konsep Pendidikan Islam Menurut Buya Hamka dan Relevansinya dengan Era Society 5.0 - Damayanti, Ellynia Ayu; Astuti, Anita Puji (Universitas Muhammadiyah Sidoarjo, 2022)
Buya Hamka explained that humans have 3 basic strengths, namely the body, soul, and mind to be able to achieve happiness in this world and in the hereafter. Education is an effort that humans can do to achieve this. Education will experience changes and developments in accordance with the development of science and technology. Entering the era of society 5.0 or the era of intelligent society, there are competencies that must be possessed in order to be able to follow the development of science and technology and stick to religious values. This study aims to determine the concept of Islamic education according to Buya Hamka and its relevance to the era of society 5. This study uses library research. Sources of data used in the form of books by Buya Hamka and several other sources relevant to the research. The results show that the concept of Islamic education according to Buya Hamka which leans towards the term tarbiyah which consists of the process of transfer of knowledge, character education, and potential development is relevant to the era of society 5.0